A debreceni tudományegyetem diáksegélypénztárának (Bursa Academica) alapszabályai - Király, Sándor (Gerundium, 2018)
Articles of the Student Relief Fund (Bursa Academica) of the University of Debrecen. Bursa Academica, the student welfare fund of the University of Debrecen was one of those student welfare institutions between the two world wars whose existence and operation were unknown even to those members of the general public who show interest in the history of the university. In publishing the full text of the articles of association and by prefixing an introductory essay before it, the author’s objective is to adequately clarify the essence and importance of the institution’s operation. Both in terms of its noble objectives and its activities maintained, the Bursa Academica deserves to be remembered, for it played, together with other similar institutions, an outstanding role in student life.